1 x 4 array antenna for wireless local area network (WLAN) - Adan, Fuad Hassan (2022)
In this project, a 1 x 4 wide band rectangular patch array antenna proposed and designed at frequency 2.4GHz for Wireless Local Area Network (WLAN) applications. The antenna will be designed using optimization and study of features. To construct the desired antenna, some strategies for optimizing the Microstrip Patch Antenna are investigated and executed. An antenna array is a radiating system, which consists of individual radiators and elements. Each of this radiator, while functioning has its own induction field. The elements are placed so closely that each one lies in the neighboring one’s induction field. Therefore, the radiation pattern produced by them, would be the vector sum of the individual one When designing these antennas, keep in mind the spacing between the elements as well as the length of the elements in relation to the wavelength. Microstrip patch array antenna developed still face problem with low gain , narrow bandwidth , high complexity and low efficiency therefore, this project proposes 1x4 microstrip patch array antenna that suitable for wireless local area network (WLAN) and provides less complexity, high gain, large bandwidth by using defected ground structure(DGS) technique and slots that suitable point to point communication system. The goal of this research is to create an antenna with higher gain, higher directivity, a wider bandwidth, and good efficiency using array antenna techniques, to propose array antenna that have wide bands using defected ground method and to compare the antenna performance using different techniques. The goal of this project can theoretically be achieved by using a high-quality substrate such as RT Duroid 5870, which has a low relative permittivity or dielectric constant and a higher substrate that will maximize bandwidth. but in this project using FR-4 substrate, which does not have high quality and high dielectric constant finally achieved high performance result using array antenna techniques and parametric studied. This is because the bandwidth of a Rectangular Microstrip Patch Array Antenna is determined by the dielectric constant and the substrate height. The antenna's efficiency will be improved by a low loss-tangent. The patch array also has a better directivity than the single patch. All the simulation design process has been conducted by using CST Studio Suite Software. The 1 x 4 microstrip patch array antenna has simulated gain of 6.33dBi at 2.4 GHz with the wide bandwidth 514MHz and efficiency more than 72%. Therefore The expected result from this project is achieved which was a high gain, better directivity, larger bandwidth and high efficiency.